Brian Poole and the Tremeloes or the Yardbirds: Comparing popular music in Perth and Adelaide in the early 1960s - Stratton, Jon (Department of Contemporary Music Studies, 2008)
In the final article, Jon Stratton explores trends in the charts history in Australia, specifically those in Adelaide and Perth, with a view towards presenting an understanding of the influence of English migrant populations in both centres. Broad links between employment, class and musical taste are drawn, and the very nature of these means it can be difficult to be categorical as to their ultimate veracity. In this sense the article might well be seen as provocative, and we hope it inspires further enquiry with a more ethnographic approach to methodology. This kind of research is difficult without the existence of detailed chart compilations such as those by Ryan (2003, 2007) which are used as the basis for Stratton’s analysis. With a great deal of contemporary industry statistics tied up in proprietary networks to protect commercial advantage, will such studies actually be harder in the future? Does the plethora of unfiltered information in which we wade today provide evidence for an urgent need of modern chart and consumption summaries?